Editorial for Special Issue “Linking Tectonic Setting to Sedimentological and Stratigraphic Variability” - Angelos G. Maravelis (Geosciences, 2023)
The stratigraphic evolution of sedimentary basins reveals (1) the spatial and temporal development of depositional settings; (2) the geotectonic settings; (3) the climatic conditions [...]